A graphical proof of the brouwer fixed point theorem - N. Chuensupantharat (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. By simplifying the proof in [1], we give a new proof of the Brouwer fixed point theorem without using the Tietze (continuous) extension theorem.